Flow-based Proxy NEMO solutions: an analysis of the location update cost - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Hasan, Mohammad Kamrul; Razzaque, Abdur; Chit, Su Mon (Institute of Electrical and Electronics Engineers Inc., 2019)
With the aim of comprehending inadequacies of basic NEMO (named as Network Mobility Basic Support Protocol), alternate protocols, for example, Proxy Mobile IPv6 (PMIPv6) based NEMO have been proposed via the research community. Similarly, with respect to MIPv6, results to concealment NEMO circumstances dependent on PNEMO have been worked out. Nonetheless, there is little concession to which the most ideal route is to deal with NEMO situations when utilizing PMIPv6. This paper analyzes distinctive flow-enabled Proxy NEMO solutions and characterize numerical model for assessing the location update cost in PNEMO environment so as to give knowledge in the detail of the highlights a flow-enabled PMIPv6 NEMO solutions ought to achieve. © 2019 IEEE.